2017
DOI: 10.1111/epi.13815
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Childhood Epilepsy in pediatric patients enrolled in a prospective, open‐label clinical study with cannabidiol

Abstract: Summary Recent clinical trials indicate that cannabidiol (CBD) may reduce seizure frequency in pediatric patients with certain forms of treatment-resistant epilepsy. Many of these patients experience significant impairments in quality of life (QOL) in physical, mental, and social dimensions of health. In this study, we measured the caregiver-reported Quality of Life of Childhood Epilepsy (QOLCE) in a subset of patients enrolled in a prospective, open-label clinical study of CBD. Results from caregivers of 48 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 14 publications
3
73
3
4
Order By: Relevance
“…This retention rate compares favorably to other AED trials in TREs (63%‐72%) . This is possibly due to maintenance of long‐term efficacy and/or adverse events that were generally mild; improvements in quality of life and seizure severity also have been reported with CBD, likely resulting in better retention. Withdrawals were spread relatively consistently through the study follow‐up period, and the LOCF sensitivity analysis demonstrated consistent reductions in seizure frequency when data from withdrawn patients were carried through the 96‐week visit window.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This retention rate compares favorably to other AED trials in TREs (63%‐72%) . This is possibly due to maintenance of long‐term efficacy and/or adverse events that were generally mild; improvements in quality of life and seizure severity also have been reported with CBD, likely resulting in better retention. Withdrawals were spread relatively consistently through the study follow‐up period, and the LOCF sensitivity analysis demonstrated consistent reductions in seizure frequency when data from withdrawn patients were carried through the 96‐week visit window.…”
Section: Discussionmentioning
confidence: 48%
“…This retention rate compares favorably to other AED trials in TREs (63%-72%). 9,10 This is possibly due to maintenance of long-term efficacy and/or adverse events that were generally mild; improvements in quality of life 11,12 and seizure F I G U R E 2 Percentage reduction from baseline in convulsive and total* seizures for (A) efficacy analysis set and (B) LOCF analysis. *Total seizures included convulsive seizures (ie, clonic, tonic, tonic-clonic, atonic, focal secondary generalized) and nonconvulsive seizures (ie, myoclonic, absence, myoclonic-absence, focal with and without impaired consciousness).…”
Section: Discussionmentioning
confidence: 99%
“…Significant improvements were observed compared to placebo as an add‐on therapy. Within the other 3 clinical trials of prospective open‐label design ( n = 203), CBD was administered at an average dosing of 42 mg/kg/d and significant improvements in quality of life and seizure frequency compared to baseline were observed . 3 case series and 1 case report (total n = 16) reported beneficial effects of CBD on seizure frequency, duration and severity with an average administered dose of 21 mg/kg/d …”
Section: Resultsmentioning
confidence: 99%
“…18 In the remaining 8 clinical trials of various Epilepsy was the most frequently studied medical condition, with all 11 studies describing beneficial effects of CBD in reducing the severity or frequency of seizures. 12,13,16,24,[26][27][28][33][34][35][36] Within the 4 conducted RCTs (n = 531), an average dosing of 15 mg/kg/d was used where CBD was administered successfully as an add-on therapy to usual anti-epileptic drugs. 12,13,16,24 Significant improvements were observed reported beneficial effects of CBD on seizure frequency, duration and severity with an average administered dose of 21 mg/kg/d.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, several open-label state expanded access programs (EAPs) have been initiated in order to study this formulation of CBD for the management of TRE in patients with other seizure etiologies, e.g., focal onset seizures or those with tuberous sclerosis complex (TSC) [10][11][12]. In the EAPs, in addition to improved seizure frequency (SF), improved quality of life has been reported in patients taking CBD [13]. However, the effects of CBD on seizure severity and adverse events profiles (AEPs) have not been examined to date.…”
Section: Introductionmentioning
confidence: 99%